New altitudinal record of Myotis moratellii Novaes et al., 2021 (Chiroptera, Vespertilionidae) in the northwestern foothills of Ecuador - Francisco X. Castellanos; Laura Simba; Jorge Brito (Check List)
Myotis moratellii Novaes et al., 2021 is a bat species that inhabits western Ecuador at low elevations (0–150 m a.s.l.). This study extends its northern distribution by 63 km into the foothill rainforests of the Chocó in Imbabura Province at 1,240 m a.s.l. Given the novel color patterns observed in the specimens collected, molecular approaches were necessary for species-level identification. Although the cause of this variation remains unclear, continued integrative taxonomy is critical to uncover the cryptic diversity within the genus.